Factors correlated to physical activity among diabetes type 2 patients - Aby Yazid Al Busthomy Rofi'i; Su'udi Su'udi (Intelektual Pustaka Media Utama, 2022)
Physical activity is an important strategy for the management of diabetes type 2 mellitus. However, this recommendation is related to physical barriers. Diabetes mellitus type 2 patients showed lower scores in energy use, number of steps and duration of physical activity compared to healthy individuals. This study aimed to identify factors that affected physical activity among diabetes type 2 patients. A cross-sectional design was used in this study. This study was conducted in Kabupaten Tuban, East Java, Indonesia. A total of 105 diabetes type 2 patients followed the program Prolanis from the community health center. Data was collected using paper-based questionnaires, which were aslked the demographic characteristics, knowledge about physical activity, diabetes management self-efficacy, and international physical activity questionnaire (IPAQ) during March to October, 2020. Ordinal logistic regression was used to examine the factors that affected physical activity of diabetes type 2 patients. This study found that complication, knowledge and self-efficacy have significantly affected physical activity among diabetes type 2 patients. This information is beneficial to develop nursing care interventions and approaches to increase the physical activity of patients with type 2 diabetes mellitus.